PENGARUH PENGETAHUAN KEPEMIMPINAN DAN KOMPETENSI MANAJERIAL TERHADAP EFEKTIVITAS KERJA KEPALA SEKOLAH DASAR NEGERI SEKABUPATEN ROKAN HILIR - Santari Santari; Mahdum Mahdum; Hadriana Hadriana (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to determine the effect of the variables (1) leadership knowledge on the effectiveness of the principal's work, (2) managerial competence on the effectiveness of the principal's work, (3) leadership knowledge and managerial competence together on the effectiveness of the principal's work. Research respondents were principals of public elementary schools in Rokan Hilir Regency, totaling 305 people with a sample of 173. Data was collected through questionnaires as a research instrument. The data analysis used is descriptive analysis and inferential statistical analysis. The instrument reliability coefficient was calculated using the Cronbach alpha formula. The results showed that there was a positive and significant influence of leadership knowledge on the work effectiveness of the principal of 0.707, and there was a positive and significant influence of managerial competence on the work effectiveness of the principal of 0.603. Meanwhile, together there is an effect of leadership knowledge and managerial competence on the effectiveness of the principal's work of 0.553